VILLAGE DEPENDENCY TO LOCAL GOVERNMENTS IN THE VILLAGE HEAD POSITION FILLING ACCORDING TO VILLAGE LAW - Amalia Diamantina; Fajar Ahmad Setiawan (Fakultas Hukum, Universitas Diponegoro, 2023)
The election of village heads in Indonesia is implementation of democracy and people's sovereignty in Indonesia. However, in practice, the Village Head Election is still very dependent on Regency / City Government. The aim of the study is to analyze the dependency of the Village Head filling on the Regency/City Government and the involvement of the Regency/City Regional Government in filling the position of Village Head. This study uses a normative juridical research method using a dogmatic legal approach and secondary data as the source. The results of the study indicate that the involvement of the Regency/City Government in filling the position of Village Head is the result of the concept of division of power, which is a territorial division of power adopted by the Unitary State of the Republic of Indonesia. As a result, the Regency/City Regional Government has a relatively large portion of involvement in filling the Village Head positions as regulated by applicable laws and regulations. This is what should be reduced for the sake of village development in Indonesia.